2014
DOI: 10.1177/1039856214522529
|View full text |Cite
|
Sign up to set email alerts
|

Unauthorised absences from leave from an Australian security hospital

Abstract: Attention to patient selection and risk management strategies have been effective in minimising the risk to patients and to the community as a direct result of absences without permission from authorised leave.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 11 publications
0
16
0
Order By: Relevance
“…) and high‐security inpatient services (Scott et al . ) have found that patients who abscond return to hospital a number of ways, including by themselves, with the assistance of family and friends, and through police involvement. These studies and others (e.g.…”
Section: Limitationsmentioning
confidence: 99%
“…) and high‐security inpatient services (Scott et al . ) have found that patients who abscond return to hospital a number of ways, including by themselves, with the assistance of family and friends, and through police involvement. These studies and others (e.g.…”
Section: Limitationsmentioning
confidence: 99%
“…A review comparing locked and unlocked doors found that rates of absconding were higher on open wards, but that incidents of absconding occurred mostly when consumers were on leave from the ward (Stewart & Bowers 2011). One study about absconding conducted in an Australian secure locked ward highlighted that a majority of consumers who abscond, do so when they are on unescorted leave from the ward either within hospital grounds or out in the community (Scott et al 2014). The commonly cited reasons for absconding whilst on unescorted leave include consumers feeling unsafe in the ward, potentially due to the effects of mental illness, but also due to the relationships with staff and other consumers (Muir-Cochrane et al 2013), isolation from family and friends, feeling trapped, confined, bored, or frustrated (Bowers et al 1999(Bowers et al , 2003.…”
Section: Evidence Regarding Locked Doorsmentioning
confidence: 99%
“…One study about absconding conducted in an Australian secure locked ward highlighted that a majority of consumers who abscond, do so when they are on unescorted leave from the ward either within hospital grounds or out in the community (Scott et al . ). The commonly cited reasons for absconding whilst on unescorted leave include consumers feeling unsafe in the ward, potentially due to the effects of mental illness, but also due to the relationships with staff and other consumers (Muir‐Cochrane et al .…”
Section: Introductionmentioning
confidence: 97%
“…Risk assessment. Of 15 forensic studies, most described individualised violence or offending-related risk assessment for leave purposes (Hearn, 2013;Lyall & Bartlett, 2010;Walker, 2013;Scott et al, 2014;Claxton et al, 2006;Scott & Meehan., 2016;Hilterman et al, 2011;Tully et al, 2016). Additionally, half the civil studies addressed leave risk assessment (Atkinson et al, 2002b;Atkinson et al, 1997;Bolin et al, 1968;Sensky et al, 1991;Barre, 2003).…”
Section: Study Synthesismentioning
confidence: 99%